2007
DOI: 10.1128/mcb.02407-06
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Intergenic Transcription Precedes Igh D-to-J Recombination and Is Controlled by the Intronic Enhancer Eμ

Abstract: V(D)J recombination is believed to be regulated by alterations in chromatin accessibility to the recombinase machinery, but the mechanisms responsible remain unclear. We previously proposed that antisense intergenic transcription, activated throughout the mouse Igh V H region in pro-B cells, remodels chromatin for V H -to-DJ H recombination. Using RNA fluorescence in situ hybridization, we now show that antisense intergenic transcription occurs throughout the Igh D H J H region before D-to-J recombination, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
78
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 69 publications
7
78
0
8
Order By: Relevance
“…However, it has been shown that sense and antisense transcription in the distal V H region does not depend upon Eμ (32,33), and we showed here that PAIR antisense transcription is also independent of Eμ. Thus, we predicted that it is likely that YY1 has an additional, and perhaps a more direct, effect on the regulation of antisense transcription.…”
Section: Discussionsupporting
confidence: 49%
“…However, it has been shown that sense and antisense transcription in the distal V H region does not depend upon Eμ (32,33), and we showed here that PAIR antisense transcription is also independent of Eμ. Thus, we predicted that it is likely that YY1 has an additional, and perhaps a more direct, effect on the regulation of antisense transcription.…”
Section: Discussionsupporting
confidence: 49%
“…Notably, both B and T lymphocytes have germ-line "μ0" transcripts that initiate from a promoter upstream of the most 3′ D segment (D H Q52) and run downstream through the J H segments, consistent with T lymphocytes making low levels of DJ H rear- rangements (16). In addition, pro-B lymphocytes express low levels of antisense transcripts from the D portion of the locus (17,18). Additional epigenetic modifications associated with V(D)J recombinational accessibility include DNA and/or histone modifications of particular regions and chromosomal positioning of the Ig or TCR loci within the nucleus (15,19,20).…”
mentioning
confidence: 85%
“…Following D to J recombination, non-coding transcripts are generated from the V genes (7,8). Furthermore, extensive antisense intergenic transcription occurs throughout the D and J domains before D to J, and then throughout the V domain before V to DJ recombination (9,10). Nuclear positioning may also play a role in ordered V(D)J recombination.…”
mentioning
confidence: 99%
“…E is required for efficient D to J recombination (18,19). It acts in part by activation of antisense intergenic transcription, which is abrogated in the DJ region by E deletion (10). It is unclear whether E is required for V to DJ recombination.…”
mentioning
confidence: 99%
See 1 more Smart Citation